1997
DOI: 10.1046/j.1365-2125.1997.t01-1-00591.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of methadone in healthy subjects and opiate users

Abstract: Aims There is some evidence that monitoring methadone plasma concentration may be of benefit in dosage adjustment during methadone maintenance therapy for heroin (opiate) dependence. However, the kinetics of oral methadone are incompletely characterized. We attempted to describe the latter using a population approach combining intensive 57 h sampling data from healthy subjects with less intensive sparse 24 h data from opiate users. Methods Single oral doses of rac‐methadone were given to 13 drug‐naive healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 19 publications
2
70
0
Order By: Relevance
“…Methadone: Methadone has been available for approximately a half-century (160). It is traditionally known for its role in assisting heroin addicts to exit street drug use, and in this context, its long half-life and duration of action have been known for some time.…”
Section: Dual or Multimechanism Opioidsmentioning
confidence: 99%
“…Methadone: Methadone has been available for approximately a half-century (160). It is traditionally known for its role in assisting heroin addicts to exit street drug use, and in this context, its long half-life and duration of action have been known for some time.…”
Section: Dual or Multimechanism Opioidsmentioning
confidence: 99%
“…Methadone on the other hand is distinctive because, unlike the natural opiates, this drug is not only orally efficacious (bio-availability 190%) but it is also, for most patients [27], very long-acting [28] and can thus be prescribed once daily. Therefore, prescribing methadone provides times for the narcotic receptors to become adapted to the steady-state concentration of methadone.…”
Section: Rationale For Methadonementioning
confidence: 99%
“…Methadone does not accumulate in patients with renal failure (15,21). In a single-dose study (1), the terminal elimination half-life for methadone was found to be 33 h to 46 h in healthy subjects, and it was possibly longer in a group of heroin addicts scheduled to start a methadone maintenance program. In a controlled single-dose trial (19) of methadone in eight patients with chronic pain, the mean elimination half-life was found to be 37.5 h for R-methadone and 28.6 h for S-methadone.…”
Section: Eliminationmentioning
confidence: 99%
“…There is a rapid and extensive initial distribution phase within 2 h to 3 h (15). Because of its relatively high lipid solubility, methadone is redistributed in fat stores with slow release into plasma and a prolonged elimination phase (1,12). Methadone exhibits efficient transport across the bloodbrain barrier with cerebrospinal fluid concentrations at 73% of serum concentrations (20).…”
Section: Absorption and Distributionmentioning
confidence: 99%
See 1 more Smart Citation